IS THE SENSE OF BELONGING A STRATEGIC RESOURCE FOR ADOLESCENT IDENTITY? - Giardiello, Mauro (European Scientific Journal, ESJ, 2015)
In the international literature the abstract representation of the adolescent as a product of childhood and pubertal maturation has obscured a deeper reflection on the real generational conditions of contemporary adolescents. The different situations in which adolescents are inserted imply a necessary redefinition of their sense of belonging to depart no more from the usual pre-built schemes but by a practice, become mandatory, which is that to make choices. This implies not only a high reflective capacity of adolescents to redefine the contours of the semantic of their world life but also to combine and distinguish at the same time the virtual reality from the real one. In this paper we show that for the digital natives belonging remains a criterion for defining the personality and the overall identity of the adolescent. In the light of these assumptions a pilot study (qualitative and quantitative) has been carried out among adolescents in three Italian cities with the aim to investigate the nature of the link between the adolescent growth and the sense of belonging, in order to understand if and in which terms this could be a strategic resource for identity.